New Travelling Wave solutions of the Korteweg De Vries Equation by - (G'/G') Expansion method. - Sedara, Samuel; Oluwatoyin, Ajibola Saheed (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
Exact hyperbolic, trigonometric and rational function travelling wave solutions to the Korteweg De Vries (KDV) equation using the (G'/G) expansion method are presented in this paper. More travelling wave solutions to the KDV equation were obtained with Liu's theorem. The solutions obtained were verified by putting them back into the equation with the aid of Mathematica. This shows that the (G'/G) expansion method is a powerful and effective tool for obtaining exact solutions to nonlinear partial differential equations in physics, mathematics and other applications.